Buying Decision: Halal Certificate and Product Ingridients - Pinilih, Muliasari (Faculty of Economics and Business, Jenderal Soedirman University, 2024)
The address of this research is to analyze the significance of halal certificates and product composition on purchasing decisions for food products in SMEs via social media. Data was seized using a questionnaire distributed to 103 respondents. The data was analyzed using the Least Square Regression Method using the t-test and F-test approaches. The outcomes of the analysis show that halal certificates are partially able to influence decisions to purchase food products in SMEs via social media and product composition can influence decisions to purchase food products in SMEs via social media. The results of the simultaneous analysis found that halal certificates and product composition were able to influence purchasing decisions for food products in SMEs via social media. The variable that has the most influence on the decision to purchase food products in SMEs via social media is halal certificate.